Mapping XML Schema to Entity Relationship and Extended Entity Relationship Models. (15th January 2008) - Bagui, Sikha
In this paper, we conceptually model an Entity Relationship (ER) diagram and Extended Entity Relationship (EER) diagram from XML Schema. This conceptual view of XML Schema is a necessary step in understanding XML data, and can easily be used to translate XML data to the relational model. Once in the relational model, XML data can avail of mature relational database technology.